A comparison of ball velocity in different kicking positions with dominant and non-dominant leg in junior soccer players. - Marques, M. C.; Pereira, F.; Marinho, D. A.; Reis, M.; Cretu, M.; van den Tillaar, R. (Journal of Physical Education and Sport, 2011)
Problem Statement: The aim of this study was to compare the ball velocity in different kicking conditions with dominant and non-dominant leg in junior soccer players. Approach: Sixteen junior soccer players (age 17.6±0.6yr, height 1.76±0.06m, and weight 67.9±5.2kg) participated in this study. All participants kicked a soccer ball three times in seven conditions with the dominant and non-dominant leg. 1) Kicking the ball from 11m straight forwards, 2 and 3) kicking the ball from 11m to the left and right side of the goal, 4 and 5) kicking the ball straight forwards from 11m after a pass from the left and right side, 6 and 7) kicking the ball straight forwards from 11m after a pass that came from a diagonal position (45º) from the left and right side. The highest ball velocity was used for analysis. Results: Significant differences were found in ball velocity between the dominant and non-dominant leg in all conditions (p<0.001). For the dominant leg also significant differences were found in the kicking of eleven meters (ideal conditions) compared with: the perpendicular passing kick after the ball on the right (p=0.0024) and left (p=0.0080) and also with a diagonal kick after pass (45 °) of the ball on the right (p=0.0017) and left (p = 0.0381). Significant differences in the kicking with the non-dominant leg were found when kicking from eleven meters to the right side of the goal in comparison to: the kick under the same conditions, to the left side of the goal (p=0.0243) after pass and shot from the left side perpendicular (p=0.0222). Conclusions/Recommendations: kicking velocity is influenced very much under different conditions when kicking with the dominant leg while for the non-dominant leg this influence was small, because the nondominant leg is less trained, so the values of velocity in different conditions, in addition to being the lowest, are closer than those obtained with the dominant leg.